2021
DOI: 10.1007/s00029-021-00631-8
|View full text |Cite
|
Sign up to set email alerts
|

The topological nilpotence degree of a Noetherian unstable algebra

Abstract: We investigate the topological nilpotence degree, in the sense of Henn–Lannes–Schwartz, of a connected Noetherian unstable algebra R. When R is the mod p cohomology ring of a compact Lie group, Kuhn showed how this invariant is controlled by centralizers of elementary abelian p-subgroups. By replacing centralizers of elementary abelian p-subgroups with components of Lannes’ T-functor, and utilizing the techniques of unstable algebras over the Steenrod algebra, we are able to generalize Kuhn’s result to a large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…In [Kuh07] and [Kuh13], Kuhn used it to approximate the depth of K as well as invariants d 0 (K) and d 1 (K) introduced by Henn, Lannes and Schwartz in [HLS95], in the case where K is the cohomology of a group. Heard generalised those results for K noetherian in [Hea20] and [Hea21].…”
Section: The Centre Of An Unstable Algebrasupporting
confidence: 54%
See 4 more Smart Citations
“…In [Kuh07] and [Kuh13], Kuhn used it to approximate the depth of K as well as invariants d 0 (K) and d 1 (K) introduced by Henn, Lannes and Schwartz in [HLS95], in the case where K is the cohomology of a group. Heard generalised those results for K noetherian in [Hea20] and [Hea21].…”
Section: The Centre Of An Unstable Algebrasupporting
confidence: 54%
“…In [Hea21], Heard showed that for K noetherian, K admits a unique (up to isomorphism) central element (C, γ) such that γ induces a structure of finitely generated K-module on H * (C) and dim(C) is maximal among such central elements. Heard called this central element the centre of K. The centre of an unstable algebra have been shown to be an important invariant.…”
Section: The Centre Of An Unstable Algebramentioning
confidence: 99%
See 3 more Smart Citations